脳血流からみた透過型情報提示デバイスの使用に伴う負担度評価 - 須藤 正時; 深谷 晃輔 (Bulletin of Japanese Society for the Science of Design, 2016)
This study modeled an information support environment through sound visualization using a see-through information presentation device and evaluated the related mental workload. Brain activation measured by cerebral blood flow was used as a physiological index. Increased cerebral blood flow was observed in response to information presentation during sound discrimination and localization tasks. Moreover, response times in both tasks were within the range of human perception-reaction time required for danger avoidance. During the rear-visibility task, responses were slower than the safety standards. In regard to the sound discrimination task, subjects were categorized according to whether they reacted faster to the vocal auditory information or to the pictorial visual information. A correlation was also observed between increased cerebral blood flow and decreased response time. Thus, information presentation that promotes brain activation associated with attentional shifting is important for enabling a shift to safety responses or actions. 本研究では透過型情報提示デバイスを用いた音の可視化による情報保障環境をモデル化し，その際の精神的作業負担（メンタルワークロード）の評価を行った。生理的指標として前頭連合野の脳血流による脳賦活状態を計測した。その結果，音源識別タスク，音源定位タスクでは情報提示に対する脳血流の増加が観測され，情報認知による神経活動の亢進が確認できた。また両タスクにおける反応時間は１秒以内であり，危険回避に対する人の知覚反応時間の範囲に収まる結果となった。後方視界タスクでは安全基準からの遅延が見られた。音源識別タスクについては，音声の聴覚情報に対し速く反応する被験者と絵文字の視覚情報に対し速く反応する被験者の２つのグループに分けられた。さらに脳血流の増加と反応時間の短縮に相関が認められた。したがって安全な反応や行動の切り替えを行うためには，注意の切り換えを促進させるような脳の賦活化を伴う情報提示が必要となることが示唆される。